Distances walked to and from local destinations: Age-related variations and implications for determining buffer sizes. (December 2019) - Sugiyama, Takemi; Kubota, Akio; Sugiyama, Masaaki; Cole, Rachel; Owen, Neville
Abstract: Introduction: Neighborhood environmental attributes can influence health-related physical activity, particularly walking. A better understanding of the distances adults walk to local destinations is needed to identify the appropriate geospatial boundaries within which environmental attributes are measured (buffer sizes). This study sought to identify the distances adults of different ages walk to/from public transit (PT) stops, shops/services, and natural features. Methods: Data from the 2009–12 South-East Queensland Travel Survey were used. Our sample consisted of 2105 adults (18–84 years) who reported at least one home-based walking trip to/from those destinations. We reported the median (with the 20th and 80th percentiles) distances walked to/from each destination category by age groups. Multilevel regression analyses examined whether the distances walked differed by age groups. Results: Participants reported 4029 walking trips, with the median distance of 0.68 km and the 80th percentile of 1.35 km. The median walking distance (80th percentile) to/from utilitarian destinations (PT stops, shops/services) and natural features was 0.63 (1.16) km and 1.15 (2.27) km, respectively. The overall median walking distance by age groups was 0.62 km for the younger (18–34 years), 0.67 km for younger middle (35–49 years), 0.79 km for older middle (50–64 years) and 0.72 km for older (65–84 years) groups. Regression analyses found that older middle-aged adults walked significantly longer overall and to/from utilitarian destinations than any of the other age groups. Conclusions: Our findings support buffer sizes around 600–1200 m for studies examining environmental correlates of walking for utilitarian purposes. For recreational walking to get to natural features, larger buffer sizes ranging from 1200 to over 2000 m may be suitable. We did not find consistent evidence supporting the use of different buffer sizes for different age groups. Highlights: Of the total home-based trips identified, 12% were walking trips (N = 4029). The median distance walked to/from public transit stops was 0.53 km. The median distance walked to/from shops and services was 0.77 km. The median distance walked to/from natural features was 1.15 km. Our findings did not support different buffer sizes for different age groups.